MERAWAT TRADISI MEMBANGUN HARMONI: TINJAUAN SOSIOLOGIS TRADISI HAUL DAN SEDEKAH BUMI DI GRESIK - Mustolehudin Mustolehudin (Research and Development Center for Guidance for Religious Societies and Religious Services, the Research and Development and Education and Training Agency of the Ministry of Religious Affairs of the Republic of Indonesia (MORA), 2014)
There are interesting patterns in Gresik’s religious social history in Gresik. Due to the existence and inheritance of Hindu-Buddhist beliefs prior to the process of Islamization undertaken by the Wali Songo, Islam in Gresik has its own unique color. The Hindu-Buddhist traditions were maintained and developed, including the tradition of Sedekah Bumi. This study seeks to understand how the social construction of the Sedekah Bumi tradition has shaped religious harmony in Gresik. Using qualitative data from in-depth interviews, observation, and an investigation of the literature, this article finds that the Sedekah Bumi tradition has become one of the ways to cultivate social cohesiveness in the community. This study also finds that the Sekedah Bumi tradition practiced by the those in the coastal areas tend to have an Islamic character. In contrast, the practices in the Southtend to have a Kejawen Islamic character.